A Patient with 38 Years of Smoking History and Severe Shortness of Breath - E. R. Buklis; N. I. Kokina; E. L. Bueverova; M. V. Feldsherov; V. S. Komarova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present a clinical case of post-COVID bronchiolitis in an adult.Key points. A 54-year-old female patient with a long history of smoking was hospitalized in the pulmonology department of the Clinic with a leading complaint of progressive shortness of breath after a COVID-19 infection. The diagnosis was established: bilateral bronchiolitis associated with a new coronavirus infection (SARS-CoV-2 polymerase chain reaction — positive); chronic obstructive pulmonary disease stage II according to GOLD (Global Initiative for Chronic Obstructive Lung Disease), exacerbation. Against the background of the therapy, there was a significant positive dynamics in well-being and in CT-picture of bronchiolitis. The patient was discharged for outpatient follow-up treatment. One of the most common symptoms of post-COVID syndrome is shortness of breath. Diagnosis of bronchiolitis, in which this symptom may be the only one, is difficult, especially in patients with a long history of smoking and the presence of comorbid pulmonary pathology.Conclusion. A clinical case of bilateral bronchiolitis in the framework of the post-COVID syndrome is presented. The key to successful diagnosis of bronchiolitis is a thorough differential analysis of the totality of anamnestic and clinical laboratory data, as well as a characteristic CT pattern.